A highly stretchable, transparent, notch-insensitive self-healing elastomer for coating. Issue 6 (8th January 2020) - Zhang, Lun; Wang, Dong; Xu, Liqiang; Zhang, Xueqian; Zhang, Aimin; Xu, Yu
Abstract : To date, transparent polymeric elastomers with high mechanical toughness and excellent self-healing ability have shown attractive prospects in various fields. Abstract : To date, transparent polymeric elastomers with high mechanical toughness and excellent self-healing ability have shown attractive prospects in various fields. However, it is difficult to balance the trade-off between self-healing and mechanical performance, and it is even harder to get a transparent one. Herein, novel polyurea materials, which were cross-linked by rationally designed multi-strength hydrogen bonding interactions as well as covalent bonds, were developed. Covalent cross-links enabled high strength, while multi-strength hydrogen bonds as dynamic cross-links ensured elasticity, energy dissipation and rapid self-healing at room temperature. The designed polymer exhibited exceptional mechanical properties such as high elongation at break (over 1600%), notch-insensitive stretchability (800%), and high toughness of 12 500 J m −2 . Additionally, it was observed that the polymer could achieve up to 100% self-healing efficiency after 6 h without any external stimuli and an average transmittance of 92.8% at a film thickness of only 1.3 mm. After scratching, the film could still regain its transparency. Notably, this robust, transparent, stretchable, and self-healing elastomer can be employed as an optical protective coating against damage and will open a new avenue for next-generation sustainable optical-electrical and display screen devices.